Turning the Hinge of Fate: Good Source and the UK-U.S. Intelligence Alliance, 1940–1942. - Jenner, C. J. (Diplomatic History, 2008)
The article discusses the diplomatic mission of United States Colonel Bonner Fellers to Cairo, Egypt in 1942 during World War II and the security breach that occurred with Fellers's communications back to the U.S. government in Washington, D.C. The author highlights the relationship between the British and American governments in the security issues that involved massive amounts of intelligence concerning British troops in Africa being leaked to the Axis countries, particularly Germany. The author also draws attention to the special nature of the relationship between the U.S. and British governments.